Western European Military Practices and Technologies in Ukraine in XVIII Century - Oleksii Sokyrko (Європейські історичні студії, 2019)
The “Military Revolution”, which became a concentrated manifestation of Europe’s political leadership during the XVIIth – XVIIIth centuries, produced new realities in the military sphere: regular armies, subordinated and held by centralized states, unified arms and clothing, division into types of military forces, special drill and education for soldiers and officers. Leadership in military technology consisted of fortifications and artillery that developed in the direction of increasing technical capacity, unification and standardization of new weapons. New approaches to the organization of the armed forces changed the character of wars.